Feeding the Campus Craze: Unpacking the Influencers on University Students’ Fast-Food Delivery Choices——An In-Depth Qualitative Exploration - Adzovie , Daniel Edem; Jibril, Abdul Bashiru; Adzovie , Rita Holm (Journal of Intelligent Communication, 2024)
One very essential tool for the success of any business operation is a good knowledge of the consumer behaviour of its target. Consumer behaviour encompasses the various actions, thoughts, and emotions that impact individuals’ decisions related to the purchase, usage, and disposal of goods and services in their daily lives. While existing literature extensively covers consumer decision-making processes, there is a noticeable lack of information on the factors influencing the decision-making processes of university students, particularly in a developing country like Ghana. To address this gap, the present study investigates the factors influencing the decisions of University of Cape Coast (UCC) students when choosing specific fast-food delivery vendors. Utilizing one-on-one interviews, a purposive sample of 12 University of Cape Coast students was selected to gather their perspectives. The findings from these interviews indicate that the primary factors influencing students’ choices to engage with fast-food delivery services are convenience/proximity, timely delivery, and the taste of the food. Additionally, sub-categories such as the quantity of food, packaging, and the appearance of delivery motor riders were identified. The outcomes of this study have implications for marketing communications, highlighting the importance of addressing factors like convenience, timely delivery, and taste to effectively engage university students in the context of fast-food delivery services.